Bioavailability and hepatoprotection enhancement of berberine and its nanoparticles prepared by liquid antisolvent method - Sahibzada, Muhammad Umar Khayam (Saudi J Biol Sci, 2021)
The study was devised to prepare berberine nanoparticles by anti-solvent precipitation method and were assessed for their hepatoprotective effect in Male Sprague-Dawley rats against carbon tetrachloride. The pharmacokinetic parameters of the prepared nanoparticles and berberine were evaluated in rabbits. Histopathological studies and blood biochemical analyses were carried out to evaluate the role of both forms of berberine in the experimental animals. Substantial improvement in the liver function test enzymes levels and liver histopathology were achieved in the animals treated with berberine nanoparticles in comparison to the unprocessed berberine whereas, pharmacokinetic parameters for nanoform of berberine were about 3.97 and 3.88 folds higher than that of the unprocessed berberine. The study revealed that the reduction of berberine particle size to nano range improved pharmacokinetic parameters in rabbits. The nano berberine provided better liver protection in experimental rats and high berberine blood concentration. Thus, better hepatoprotective and pharmacokinetics effects were observed for the nano form in comparison to unprocessed form.